Inhibitory effect of opiates on LPS mediated release of TNF and IL-8. (June 2013) - Bastami, Salumeh; Norling, Cecilia; Trinks, Cecilia; Holmlund, Birgitta; Walz, Thomas M.; Ahlner, Johan; Uppugunduri, Srinivas
Abstract Most patients with advanced cancer experience severe pain and are often treated with opiates. Cancer patients are especially susceptible to opportunistic infections due to treatment with immunosuppressive and cytostatic drugs. Since opiates have been demonstrated to have immunomodulatory effects, it is of clinical importance to evaluate potential differences between commonly used opiates with regard to their effect on the immune system. The aim of this study was to evaluate the effect of morphine, tramadol, fentanyl and ketobemidone on the functioning of the immune system with special reference to TNF and IL-8 release. Method. U-937 cells were preincubated with different concentrations of opioids followed by stimulation with LPS 100 μg/ml for three hours. The effect of opioids on the levels of cytokine mRNA was studied using RT-PCR. Erk and Akt phosphorylation was also measured by Western blot. Results. All opioids with the exception of fentanyl were capable of inhibiting TNF release from U-937 cells. Morphine had no effect on IL-8 release but the effect of other opiates was almost the same as the effect on TNF. All opioids with the exception of fentanyl were capable of inhibiting production of mRNA for TNF and IL-8. The observed effects of opiates were not always reversible by naloxone, suggesting that the effects might be mediated by other receptors or through a non-receptor mediated direct effect. Although preliminary evidence suggests the involvement of Erk and Akt pathways, further studies are needed to unravel the intracellular pathways involved in mediating the effects of opiates. Our data suggests that the order of potency with regard to inhibition of cytokine release is as follows: tramadol > ketobemidone > morphine > fentanyl. Conclusion. Further studies are needed to understand the clinical implications of the observed immunosuppressive effects of tramadol and ketobemidone and to improve opioid treatment strategies in patients with cancer.